Kesadaran Sosial Masyarakat Masa Pandemi; Kajian Religiusitas di Sleman Yogyakarta - Salim, Ahmad Salim; Salekhah, Rahmai Aida Viv (Literasi: Jurnal Ilmu Pendidikan, 2022)
KESADARAN SOSIAL MASYARAKAT MASA PANDEMI; KAJIAN RELIGIUSITAS DI SLEMAN YOGYAKARTAABSTRACTThis study discusses the Social Awareness of the Community during the Pandemic; Religiosity Studies in Sleman Yogyakarta. The research was qualitative research. In this study, researchers used Forland's theory related to social awareness in society and the theory of religiosity used the theory of Chaplin, and Ananto in Thontowi. Social awareness is an awareness that exists in a person and is owned thoroughly for his rights and obligations. Social awareness that exists within the community can grow because of a sense of alertness to certain social conditions, where these conditions are experienced by themselves or others in the surrounding environment. Especially during the Covid-19 pandemic like this, social awareness is very much needed in society, especially in the aspect of religiosity. Where people become more frequent in praying and asking to God, this is done to take care of each other, and as a form of endeavor to protect themselves and the environment they live in. The results of this study indicate that the level of social awareness of the community during the pandemic and the religiosity of the community has changed and increased, then the majority of the motives for the existence of social awareness and religiosity are merely carrying out alms because of the pleasure of worshiping of God, and on the basis of the existence of religiosity in servant to God then people do not find obstacles to charity